2005
DOI: 10.1016/j.femsle.2005.01.052
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio choleraepersistence in aquatic environments and colonization of intestinal cells: involvement of a common adhesion mechanism

Abstract: Forty-one Tnpho A mutants of Vibrio cholerae O1 classical strain CD81 were analyzed for their ability to interact with chitin particles, Tigriopus fulvus copepods and the Intestine 407 cell line compared to the parent strain. Thirteen mutants were less adhesive than CD81; in particular, T21, T33 and T87 were less adhesive towards all substrates and insensitive to inhibition by N-acetyl glucosamine (GlcNAc). By SDS-PAGE analysis of sarkosyl-insoluble membrane proteins (siMPs) isolated from mutants and parent, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 39 publications
1
50
0
2
Order By: Relevance
“…V. cholerae is known to adhere to different surfaces, such as the human lumen (20), chironomid egg masses (6), chitin (46), zooplankton (9,18), and cornstarch granules (15). Its ability to adhere is related to the survival of the bacteria in the environment (9), as it facilitates both adherence to available nutrition sources and protection against environmental stresses (52). It is also associated with colonization in the human intestine, which is a prerequisite for establishment of a productive infection (20,41).…”
Section: Discussionmentioning
confidence: 99%
“…V. cholerae is known to adhere to different surfaces, such as the human lumen (20), chironomid egg masses (6), chitin (46), zooplankton (9,18), and cornstarch granules (15). Its ability to adhere is related to the survival of the bacteria in the environment (9), as it facilitates both adherence to available nutrition sources and protection against environmental stresses (52). It is also associated with colonization in the human intestine, which is a prerequisite for establishment of a productive infection (20,41).…”
Section: Discussionmentioning
confidence: 99%
“…Two of our environmental strains (EVC4 and EVC5) with tcpA 2 /toxT 2 genotype showed strong adhesive properties to the cells. Non-fimbrial adhesive factors such as MSHA (mannose sensitive haemagglutinin antigen) and 53 kDa CBP (chitin binding protein) have been suggested as colonization factor candidates (Kirn et al, 2005;Zampini et al, 2005;Vezzulli et al, 2008). Other colonization factors such as TcpF, TcpI and AcfB have recently been identified (Kirn et al, 2003;Chaparro et al, 2010).…”
Section: Autoagglutination and Adherence Assaymentioning
confidence: 99%
“…Compared to freeliving organisms, organisms associated with zooplankton have been shown to be different in morphology, size and metabolic activity (Tarsi et al 2000 cagA plankton provides stable microhabitats for microorganisms in which cells are more likely to survive stressful conditions found in seawater than in free form (Huq et al 1983, Colwell & Huq 1994, WinieckaKrusnell et al 2002. This assumption is supported by numerous studies on pathogenic bacteria other than Helicobacter pylori, in which the ecological relationship between epibiotic microorganisms and copepods results in protection from stress conditions (Signoretto et al 2004, Zampini et al 2005. Zooplankton can therefore be a reservoir for pathogenic bacteria such as Vibrio spp., including V. cholerae (Colwell & Huq 1994).…”
Section: Discussionmentioning
confidence: 92%
“…Vibrio spp. mineralize chitin-containing substrates (Pruzzo et al 1996, Tarsi et al 2000, and thus have been found to be associated with chitincontaining copepods such as Tigriopus fulvus (Pruzzo et al 2003, Zampini et al 2005. The identification of the environmental strain obtained by using the species-specific target gene vacA and the confirmatory DNA sequencing indicated that the isolate was a true Helicobacter pylori strain.…”
Section: Discussionmentioning
confidence: 99%